(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدف الباحث من خلال دراسته تحديد فعالية العوامل الإدارية في تطبيق نظام النقل المتعدد الوسائط، إلى تحديد فعالية العوامل اللوجستية في تطبيق هذا النظام، وتقييم مدى كفاءة البنية التحتية اللازمة لتطبيق هذا النظام، واعتمد الباحث في اختبار فرضياته على بيانات أولية تم الحصول عليها من خلال توزيع استبانة على المتعاملين مع محطة حاويات مرفأ اللاذقية من مخلصين جمركين وشركات ملاحية،حيث بلغ عدد أفراد العينة 60. استخدم الباحث اختبار ستيودنت كعينة واحدة لاختبار فرضياته، كما قام بإجراء توصيفات ديمغرافية لأفراد العينة، حيث بلغ معامل ألفا كرونباخ لقياس الثبات 0,911، وخلصت الدراسة إلى تدني الخدمات اللوجستية في محطة حاويات مرفأ اللاذقية وضعف الكوادر البشرية المؤهلة والمدربة على استخدام هذا الأسلوب من النقل. وتوصل الباحث في نهاية دراسته إلى ضرورة تحديث كافة البنى التحتية الخاصة بكل وسط، وإلى الاستفادة من الموقع الجغرافي السورية. The research aims through his studies to determine the effectiveness of the administrative factors in the application of multi-modal transport system. He also aims to determine the effectiveness of logistical factors in the application of this system, and assess the extent of the efficiency of the nessessary infrastructure for the application of this system. The researcher adobted to test his hypotheses on the preliminary data obtained through a distribution of a questionnaire to the workers of the container terminal of the Port of Latakia, the customs agents and shipping companies, and the number of the respondents was about 60 people. The researcher used the "Student" test sample as one sample in order to test his hypotheses. He conducted demographic descriptions for the members of the sample,Cronbach’s alpha coefficient to measure the stability was 0,911. The study concluded: Poor logistic service in the container terminal at the Port of Latakia and the weakness of qualified and trained staff to use the method of transport. The researcher found at the end of the study: The need to update all the infrastructure related to each place and take advantage of the geographical location of Syria.